2023
DOI: 10.3390/ijerph20054549
|View full text |Cite
|
Sign up to set email alerts
|

Association between Outdoor Air Pollution and Fatal Acute Myocardial Infarction in Lithuania between 2006 and 2015: A Time Series Design

Abstract: Background. Air pollution has a significant effect on human health and there is a broad body of evidence showing that exposure to air pollution is associated with an increased risk of adverse health effects. The main objective of this study was to assess the association of traffic-related air pollutants with fatal AMI during the ten-year period. Methods. The study was conducted in Kaunas city, where the WHO MONICA register included a total of 2273 adult cases of fatal AMI cases during the 10-year study period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…This study showed a correlation between levels of PM10 and the frequency of referrals for specific UA disorders, suggesting that PM10 can help forecast and manage health-related effects. The study conducted by Vaičiulis et al [7] found that higher PM10 levels in the air, occurring 5-11 days before acute myocardial infarction, were associated with a significant increase in the risk of fatal AMI (Acute Myocardial Infarction), particularly during the winter-spring period. Furthermore, nitrogen dioxide (NO2) is related to various health problems.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed a correlation between levels of PM10 and the frequency of referrals for specific UA disorders, suggesting that PM10 can help forecast and manage health-related effects. The study conducted by Vaičiulis et al [7] found that higher PM10 levels in the air, occurring 5-11 days before acute myocardial infarction, were associated with a significant increase in the risk of fatal AMI (Acute Myocardial Infarction), particularly during the winter-spring period. Furthermore, nitrogen dioxide (NO2) is related to various health problems.…”
Section: Introductionmentioning
confidence: 99%